Effect of two different doses of solifenacin succinate therapy (5mg, 10mg) for the treatment of ureteral stent (Double J) related symptoms in comparison to placebo - Ahmed Adil Mohammed; Shawqi Goerge Ghazala; Nihad Pauls Al-Ibraheem (Zanco Journal of Medical Sciences, 2020)
Background and objective: Double-J ureteral stent is widely used in endourologic surgery. However, it might cause some annoying side effects. This study aimed to evaluate the effect of two different doses of solifenacin (5mg, 10mg) on double-J stent-related symptoms after uncomplicated ureteroscopic lithotripsy. Methods: This study involved 120 patients. A total of 80 patients undergoing double-J ureteral stent insertion after ureteroscopic lithotripsy were involved in this study and provided with solifenacin postoperatively; 40 patients received 5mg and another 40 patients received 10mg. Another 40 age- and sex-matched patients without solifenacin therapy (received placebo) were enrolled as a placebo group. All patients completed the modified-form of the Ureteral Symptom Score Questionnaire to evaluate the lower urinary tract symptoms, hematuria and stent-related body pain two weeks following the operation. The severity of stent-related symptoms was compared between the three groups. Results: The mean age was 45.4 years in the 5 mg solifenacin group, 48.2 years in the 10 mg solifenacin group, and 46.8 years in the placebo group. Compared to the placebo group, both solifenacin groups had significantly lower total symptom score, urgency, and urge incontinence scores. Solifenacin groups had significantly less urethral, abdominal and flank pain and hematuria scores. There was no statistically significant difference between the two solifenacin groups of 5mg and 10mg. The solifenacin groups versus the placebo group showed significant benefits in lower urinary tract symptoms, hematuria, and stent-related pain in both genders. Ten subjects encountered minor adverse events in solifenacin groups (8 in the 10 mg group and 2 in the 5 mg group), which was mostly dry mouth and constipation. Conclusion: Postoperative solifenacin was effective and well-tolerated in patients undergoing ureteroscopic lithotripsy and double-J stent indwelling irrespective of genders, particularly for the treatment of stent-related body pain, hematuria and the lower urinary tract symptoms.